Analysis of Metabolite Compound Profiles of Miana Leaves Endophytic Bacteria (Coleus scutellariodes) using GC-MS - Dwi Endah Kusumawati; Fachriyan Hasmi Pasaribu; Ukhradiya Magharaniq Safira Purwanto; Maria Bintang (Current Biochemistry, 2022)
Exploration of bioactive compounds from endophytic bacteria as novel source of antibacterial need to be explored, as an alternative to substitute synthetic antibiotics. Based on previous studies, DM6 was a potential isolate that showed antibacterial activity. The isolate has been identified as Brevibacillus sp. based on 16S rRNA analysis. This study aimed to identify antibacterial compounds produced by DM6 isolate using GC-MS. The GC-MS results showed that the chloroform extract of DM6 isolate contained : 1-Octadecene (CAS).alpha.-Octadecene, Hexanedioic acid, dioctyl ester (CAS) Dioctyl adipate, Phenol, 3,5-bis(1,1-dimethylethyl)- (CAS) 3,5-Di-tert-butylphenol, and 1,4-diaza-2,5-dioxobicyclo[4.3.0]nonane. Adipic acid/hexanedioic acid and phenols are also known to contained in the leaves of Coleus scutellariodes. This indicated that endophytic bacteria were able to synthesize antibacterial compounds which similar with the host plant.